Dose effects of oral bovine colostrum supplementation on physical work capacity in cyclists - Coombes, J. S.; Conacher, M.; Austen, S. K.; Marshall, P. A. (2000)
Recent studies have reported that concentrated oral bovine colostrum protein supplementation at 60 g/day improves jumping and rowing performance and recovery in treadmill running. The purpose of this study was to determine the dose effect of bovine colostrum (IntactTM concentrated colostrum protein, NorthField Laboratories Pty Ltd) ingestion on cycling performance. Forty-two competitive cyclists were randomly divided into three groups and required to consume daily either 1) 20 g/day bovine colostrum + 40 g whey protein concentrate (wpc), 2) 60 g of bovine colostrum or 3) 60 g of wpc. Performance was assessed by two measures before (pre) and after (post) an eight week supplementation (supp.) period. The tests were designed to determine, 1) the amount of work completed in a second VO2max test as a percentage of an initial VO2max test and 2) the time to complete 2.8 kJ/kg following a two hour cycle at 65% VO2max. Subjects were required to maintain their regular training program and keep a food and training diary. Whilst results showed that subjects in all groups performed more work during a second VO2max test post supp. compared to pre supp., these improvements were not significant (placebo = 3.4%, 20 g = 4.0%, 60 g = 3.9%). Subjects in the 20g and 60g groups completed the time trial significantly (p<0.05) faster post supp. compared to pre supp. (improvements in performance times (sec), placebo = 37, 20g = 158, 60g = 134). These results indicate that oral bovine colostrum supplementation at 20g or 60g/day improves physical work capacity in cyclists. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)